The Regulation of Photosynthetic Structure and Function during Nitrogen Deprivation in Chlamydomonas reinhardtii . Issue 2 (8th December 2014) - Juergens, Matthew T.; Deshpande, Rahul R.; Lucker, Ben F.; Park, Jeong-Jin; Wang, Hongxia; Gargouri, Mahmoud; Holguin, F. Omar; Disbrow, Bradley; Schaub, Tanner; Skepper, Jeremy N.; Kramer, David M.; Gang, David R.; et al.
Abstract : Nitrogen deprivation induces orderly, multilevel down-regulation of the photosynthetic apparatus, energy capture, and carbon fixation. Abstract: The accumulation of carbon storage compounds by many unicellular algae after nutrient deprivation occurs despite declines in their photosynthetic apparatus. To understand the regulation and roles of photosynthesis during this potentially bioenergetically valuable process, we analyzed photosynthetic structure and function after nitrogen deprivation in the model alga Chlamydomonas reinhardtii . Transcriptomic, proteomic, metabolite, and lipid profiling and microscopic time course data were combined with multiple measures of photosynthetic function. Levels of transcripts and proteins of photosystems I and II and most antenna genes fell with differing trajectories; thylakoid membrane lipid levels decreased, while their proportions remained similar and thylakoid membrane organization appeared to be preserved. Cellular chlorophyll (Chl ) content decreased more than 2-fold within 24 h, and we conclude from transcript protein and 13 C labeling rates that Chl synthesis was down-regulated both pre- and posttranslationally and that Chl levels fell because of a rapid cessation in synthesis and dilution by cellular growth rather than because of degradation. Photosynthetically driven oxygen production and the efficiency of photosystem II as well as P700 + reduction and electrochromic shift kinetics all decreased over the time course, without evidence of substantial energy overflow. The results also indicate that linear electron flow fell approximately 15% more than cyclic flow over the first 24 h. Comparing Calvin-Benson cycle transcript and enzyme levels with changes in photosynthetic 13 CO2 incorporation rates also pointed to a coordinated multilevel down-regulation of photosynthetic fluxes during starch synthesis before the induction of high triacylglycerol accumulation rates.